2020
DOI: 10.1097/acm.0000000000003419
|View full text |Cite
|
Sign up to set email alerts
|

Five Questions for Residency Leadership in the Time of COVID-19: Reflections of Chief Medical Residents From an Internal Medicine Program

Abstract: The COVID-19 pandemic has drastically affected the traditional methods residency programs use to train their residents. Chief residents serve a unique role as part of the residency leadership to foster the education and development of the residents. Given the rapid shift in demands on physicians in the face of the pandemic, the responsibilities of the chief residents have also shifted to help prepare the residents to meet these demands as frontline providers. There is not a precedent for how residency programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 0 publications
3
73
0
3
Order By: Relevance
“…Though certainly there is no one-size-fits-all solution, there does seem to be a universal observation from our experience: the importance of consistent and frequent forums for convening. This is supported by recent literature where managing communication and maintaining a sense of community were identified as key components to the successful pandemic response of AMCs [14,18,20]. Connecting in person, even if virtually, was critical for both faculty and residents.…”
Section: Critical Reflectionmentioning
confidence: 59%
See 1 more Smart Citation
“…Though certainly there is no one-size-fits-all solution, there does seem to be a universal observation from our experience: the importance of consistent and frequent forums for convening. This is supported by recent literature where managing communication and maintaining a sense of community were identified as key components to the successful pandemic response of AMCs [14,18,20]. Connecting in person, even if virtually, was critical for both faculty and residents.…”
Section: Critical Reflectionmentioning
confidence: 59%
“…Put to task, medical educators worldwide have shared their experiences on the pandemic responses of their respective AMCs with insights primarily falling along three main axes: clinical service provision, preserving resident health, and educational continuity [6][7][8][9][10]. Moreover, an expanding body of literature on innovative educational strategies, trainee perspectives, and personal reflections of educational leaders has further enriched our understanding of the scale and nature of challenges faced by AMC's [11][12][13][14][15][16][17]. Nonetheless, most studies have focused on single program or institutional interventions, with a relative scarcity of information on whole system approaches that encompass regulatory, operational, and academic stakeholders.…”
Section: Background and Need For Innovationmentioning
confidence: 99%
“…Naser et al reported experience of restructuring of general surgery residents during pandemics into three exclusive groups (inpatient, operative, and clinic) rotating weekly to practice appropriate physical distancing and reduce the possibility of transmission among residents (14). pandemic (6,11,13,(15)(16)(17)(18)(19). Bambakidis reported experience of neurosurgery at Cleveland Medical Center that one or two residents to be in place with patient discussion with the team by teleconference (11).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Schwartz et al recommended post-clinic virtual conference between attendings and on-service residents (video-enabled telemedicine) for clinical education (6). Ground round webinars live interactive virtual visiting professor sessions, virtual academic conference, case-based conferences and morning session webinar, journal club webinar, email-based clinical vignettes with associated questions and clinical images, virtual live or recorded conferences were being used for clinical education in a different residency program (8,13,(15)(16)(17)(18)(19). In these different virtual teachings used in different residency programs, many recommended using different mechanisms such as using tools that promote interaction and audience participation, using the platform in which users can submit questions through a live chat function to decrease participant talk-over and allows for a more uid presentation (7,16) 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation